Medical ethics and the end of life. Euthanasia and palliative care in the Codes of Medical Ethics and Deontology. - Herranz, Gonzalo (Medicina e Morale, 1998)
The Codes of ethics and deontology of 39 national medical associations (22 from Europe and 17 from the Americas), in more than one hundred different editions, have been reviewed to identify the articles dealing with the ethics of the end of life, and specifically with euthanasia, medically assisted suicide, futile overtreatment, and palliative care. Attention has been paid not only to the current codes, but, when available, to their previous versions. According to the specificity and extension of their contents, the national medical associations have been assigned to four groups: those which do not deal with the matter, those which allude to it in a cursory way, those treating it in an explicit but incomplete manner, and finally those offering a detailed exposition. The pertinent articles have been transcribed to form an anthology. They vary greatly in style, detail and scope, reflecting the odd diversity of local concerns. But, at the same time, they reveal the deep unity of the common tradition: besides a practically unanimous rejection of euthanasia, medically assisted suicide, futile treatment, there is a general recommendation of palliative care. The author considers that such a rare unanimity must be taken in account when the attitudes of doctors towards the end of life of their patients are discussed. In his view, the complex process of drafting, discussing and approving a code of medical ethics at the level of a national medical association demands undoubtedly more soul-searching and commitment than the answering of opinion polls.